Zukunftsfähige Raumplanungsausbildung: Das Beispiel der Fakultät Raumplanung der TU Dortmund - Blotevogel, Hans Heinrich; Scholz, Tobias (Raumforschung und Raumordnung | Spatial Research and Planning, 2008)
This article deals with the adaptation of study courses to the two-cycle bachelor’s and master’s study system in planning education, according to the Bologna process. At first crucial general conditions coming along with the Bologna Reform are introduced. This contains among others the European Credit Transfer System (ECTS) and new requirements concerning the structure and duration of academic programmes. Further basic considerations on planning education are presented. The main focus of the article is on the case study about the courses of planning studies belonging to the Technische Universität Dortmund, School of Spatial Planning.